PENGGUNAAN ANALISIS RASIO DALAM RANGKA PENILAIAN KINERJA KEUANGAN KOPERASI DESA MERAH PUTIH (KDMP) BENTANGAN KECAMATAN WONOSARI KABUPATEN KLATEN - Fresiliasari, Oktavie; Suhardjo, Yohanes (Jurnal Pengabdian Masyarakat Akuntansi, Bisnis & Ekonomi, 2025)
The President of the Republic of Indonesia for the 2024-2029 period, Prabowo Subianto, announced the launch of 80,000 village cooperatives under the name of the Merah Putih Village/Sub-district Cooperative. The KDMP Bentangan, Wonosari District, Klaten Regency, is a KDMP established by the Bentangan village community, Wonosari District, Klaten Regency, as an embodiment of Presidential Instruction Number 9 of 2025 concerning the Acceleration of the Establishment of Village/Sub-district Cooperatives. In carrying out its activities, the financial aspects of cooperatives can be analyzed through financial reports. Cooperative financial reports present the cooperative's financial performance in a structured manner that is useful for making decisions by cooperative managers. Cooperative financial performance can be measured using ratio analysis. The financial ratios that can be used to measure cooperative financial performance are the liquidity ratio, profitability ratio, and solvency ratio. In order to improve the understanding of KDMP Bentangan Management and Employees regarding the use of ratio analysis for assessing cooperative financial performance, a Community Service Activity was carried out, namely Training on the Use of Ratio Analysis for Financial Performance Assessment at KDMP Bentangan, Wonosari District, Klaten Regency on Saturday, October 25, 2025, which was attended by KDMP Bentangan management and employees. The training activity was carried out by presenting material regarding ratio analysis methods, cooperative financial performance and the implementation of ratio analysis to assess cooperative financial performance. After the presentation of the material, it was continued with a question and answer session between the resource person and participants. During the activity, participants followed the activity until it was finished and actively asked questions related to the material presented by the resource person.